2018
DOI: 10.7566/jpsj.87.064005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Edge on-Site Potential in a Honeycomb Topological Magnon Insulator

Abstract: The difference between the edge on-site potential and the bulk values in a magnonic topological honeycomb lattice leads to the formation of edge states in a bearded boundary, and the same difference is found to be the responsible for the absence of edge states in a zig-zag termination. In a finite lattice, the intrinsic on-site interactions along the boundary sites generate an effective defect and Tamm-like edge states appear for both zig-zag and bearded terminations. If a non-trivial gap is induced, Tamm-like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Compared to previous studies [29][30][31]33], we here adopt a more general form for the solutions, suitable for bounded systems. These phase factors along the x-axis are intrinsic to the phase field matching theory [16][17][18][19][20][21].…”
Section: Field Theory Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous studies [29][30][31]33], we here adopt a more general form for the solutions, suitable for bounded systems. These phase factors along the x-axis are intrinsic to the phase field matching theory [16][17][18][19][20][21].…”
Section: Field Theory Formulationmentioning
confidence: 99%
“…Real and imaginary solutions correspond to evanescent and bulk exchange spin wave modes respectively. Note that in our approach, the boundary conditions are solved simultaneously on both edges, unlike previous approaches[29][30][31]33] where the boundary conditions are solved separately on the edges, similar to the semi-infinite lattice case.For the imaginary solutions, it is convenient to substitute = ( is the wavevector component along the x-direction) in equations(12) and get the equivalent equations can be easily shown that none of equations(14) admit continuous solutions in for finite ̃ and . The wavevector along the nanoribbon bounded width 2 is hence discrete and the number of solutions depends on this width.…”
mentioning
confidence: 99%
“…Nonreciprocal spin waves have received intensive theoretical and experimental attention in view of their importance for technological applications [20][21][22][23][24]. The important recent discovery of magnetic properties in Dirac materials attracted substantial interest in their magnetic excitations [25][26][27][28][29][30][31][32][33][34][35][36][37]. The novel characteristics for magnetic excitations in Dirac materials is believed to open important new opportunities in the field of magnonics.…”
Section: Introductionmentioning
confidence: 99%
“…Solving the bulk equations of motion consistently with the boundary conditions yields the edge and discretized bulk exchange spin waves for both types of nanoribbons in the long wavelength part of the Brillouin zone. Unlike previous theoretical studies [25,33,34,37] where the boundary conditions are derived and solved on one edge of the nanoribbon, in our approach the derived boundary equations are solved simultaneously on both edges. Edge spin waves are obtained for both types of nanoribbons, with and without magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…is the exchange constant and ≥ 1 is the anisotropy parameter along the z-axis. The parameter determines the strength of the DMI, whereas the orientation of ⃗ ⃗⃗ in the honeycomb lattice is determined in the conventional way from the local geometry for a nonzero output with reference to the ribbon spin vectors [40,48,58].…”
Section: Resultsmentioning
confidence: 99%